2001
DOI: 10.1016/s0092-8674(01)00313-0
|View full text |Cite
|
Sign up to set email alerts
|

The CaMKII UNC-43 Activates the MAPKKK NSY-1 to Execute a Lateral Signaling Decision Required for Asymmetric Olfactory Neuron Fates

Abstract: A stochastic cell fate decision mediated by axon contact and calcium signaling causes one of the two bilaterally symmetric AWC neurons, either AWCL or AWCR, to express the candidate olfactory receptor str-2. nsy-1 mutants express str-2 in both neurons, disrupting AWC asymmetry. nsy-1 encodes a homolog of the human MAP kinase kinase kinase (MAPKKK) ASK1, an activator of JNK and p38 kinases. Based on genetic epistasis analysis, nsy-1 appears to act downstream of the CaMKII unc-43, and NSY-1 associates with UNC-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
197
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(203 citation statements)
references
References 35 publications
5
197
1
Order By: Relevance
“…Genomic data of C. elegans was listed out the candidate components of the JNK and p38 pathways in C. elegans by comparison to mammalian homologs, and corresponding C. elegans mutants (Brenner et al, 1974;Kawasaki et al, 1999;Koga et al, 2000;Byrd et al, 2001;Sagasti et al, 2001;Sakaguchi et al, 2004;Nakata et al, 2005;Troemel et al, 2006). To confirm that jkk-1 is not involved in a response to the P. aeruginosa infection, and to find out whether other MAPKKKs and MAPKKs are involved in the response to pathogenic infections, we constructed RNAi plasmids for some of these candidate genes, as listed in Table 1.…”
Section: Elegans Mapkk Mkk-4 Is Required In the Activation Of Pmk-mentioning
confidence: 99%
“…Genomic data of C. elegans was listed out the candidate components of the JNK and p38 pathways in C. elegans by comparison to mammalian homologs, and corresponding C. elegans mutants (Brenner et al, 1974;Kawasaki et al, 1999;Koga et al, 2000;Byrd et al, 2001;Sagasti et al, 2001;Sakaguchi et al, 2004;Nakata et al, 2005;Troemel et al, 2006). To confirm that jkk-1 is not involved in a response to the P. aeruginosa infection, and to find out whether other MAPKKKs and MAPKKs are involved in the response to pathogenic infections, we constructed RNAi plasmids for some of these candidate genes, as listed in Table 1.…”
Section: Elegans Mapkk Mkk-4 Is Required In the Activation Of Pmk-mentioning
confidence: 99%
“…In contrast, in wild-type worms, only one of the two neurons expresses this gene ( 19 -21 ); the asymmetry may contribute to the worm ' s ability to mount an adaptive directional response to environmental cues. Epistasis analysis suggested that TIR-1 may infl uence olfactory neuronal development at a step between UNC-43, a calmodulin-dependent protein kinase II homologue, and NSY-1, a homologue of human ASK1, which is a MAP kinase kinase kinase ( 18,22 ).…”
Section: Myd88-5 Is Expressed In Neuronsmentioning
confidence: 99%
“…In C. elegans, calcium signaling through a voltage-dependent calcium channel and UNC-43 calcium/calmodulin-dependent protein kinase type II (CaMKII) determines asymmetric expression of the candidate odorant receptor gene str-2 in a specific bilateral pair of olfactory neurons (Troemel et al, 1999). NSY-1, the C. elegans homolog of ASK1, has been found to function downstream of UNC-43 CaMKII in the control of asymmetric expression of str-2, odor discrimination and odor chemotaxis, suggesting the possible involvement of ASK1 in the functional differentiation of the nervous system (Sagasti et al, 2001;Wes and Bargmann, 2001). NSY-1 has also been identified as a signaling component required for anti-bacterial response in C. elegans; nsy-1 mutant shows enhanced susceptibility to killing by Pseudomonas aeruginosa (Kim et al, 2002).…”
Section: Emerging Roles Of Ask1 Beyond the Pro-apoptotic Signaling Inmentioning
confidence: 99%
“…Overexpression of wild-type or constitutively active ASK1 induces apoptosis in various cells through mitochondria-dependent caspase activation Kanamoto et al, 2000;Hatai et al, 2000), and ASK1 is required for apoptosis induced by oxidative stress, TNF and endoplasmic reticulum (ER) stress Nishitoh et al, 2002). On the other hand, several lines of evidence have suggested that ASK1 has diverse functions in the decision of cell fate such as differentiation and survival (Sayama et al, 2000;Takeda et al, 2000;Sagasti et al, 2001;Kim et al, 2002). Thus, ASK1 appears to be a pivotal component not only in stressinduced cell death but also in a broad range of biological activities.…”
mentioning
confidence: 99%